Battery innovation and the Circular Economy - Metzger, Philipp (2023)
Metzger, P., Mendonça, S., Silva, J. A., & Damásio, B. (2023). Battery innovation and the Circular Economy: What are patents revealing? Renewable Energy, 209(June), 516-532. https://doi.org/10.1016/j.renene.2023.03.132---Funding: Bruno Damásio and Philipp Metzger acknowledge the financial support provided by Fundac̨ão para a Ciência e a Tecnologia, Portugal (FCT) under the project UIDB/04152/2020 — Centro de Investigação em Gestão de Informação (MagIC). Sandro Mendonça acknowledges support by FCT, Portugal, by the Business Research Unit (BRU-IUL) and by UECE-REM (Research Unit on Complexity and Economics). BRU-IUL also benefited from grants UID/GES/00315/2013, UIDB/00315/2020; UIDB/05069/2020; PTDC/EGE-ECO/30690/2017 and is part of the project PTDC/EGE-ECO/30690/2017. José Silva acknowledges FCT support under the project UIDB/50019/2020–IDL.